Management of solid waste during the pandemic COVID-19 in the region of Amazon Western, Brazil (Research, Society and Development, 2022)
The World Health Organization (WHO) pointed out that the pandemic COVID-19 infected more than 364 million peo-ple, with the number of deaths exceeding 5.6 million people. In this scenario, Brazil was one of the most affected wor-ldwide by the pandemic COVID-19, which had adverse effects on the environment, public health and economic aspects. This study aimed to evaluate the potential environmental impacts caused by the generation of urban solid waste during the COVID-19 pandemic in the Amazon region, having as a case study the municipality of Humaitá, in the state of Ama-zonas. The study corresponds to a qualitative analysis, where initially, a bibliometric review was carried out regarding solid waste management during the pandemic COVID-19. The assessment of the impacts on the solid waste management system in the municipality of Humaitá was based on qualitative-quantitative characterization data, in addition to the estimation of the number of face masks discarded daily in the municipality. The results of state-of-the-art for solid was-te management in the pandemic COVID-19, showed that research on waste management in the pandemic COVID-19 period is incipient in the Amazon region. It was possible to observe an estimate of approximately 49 thousand face masks discarded daily in the municipality of Humaitá, Amazonas, these scenarios converge to the increase of environ-mental and public health damages. From this study, it was possible to infer that the pandemic COVID-19 can point to a series of adversities on the solid waste management system, with environmental, economic, sanitary and social conse-quences.